Mobile Data Logger with GPS Feature for Ground Atmospheric Measurement - Muhammad Abu Bakar Sidik; Mohd Qamarul Arifin Rusli; Zuraimy Adzis; Zolkafle Buntat; Yanuar Arief; Hamizah Shahroom; Zainuddin Nawawi; Muhammad Irfan Jambak (IAES Indonesia Section, 2014)
The data logger system plays an important role in research and development. In order to obtain valid data, the data logger must be reliable and effective. High investment costs are involved in acquiring a data logger, and choosing a suitable data logger is difficult. In this paper, a mobile data logger is developed by using Arduino-Uno. This mobile data logger is equipped with a GPS module, which provides accurate positioning in the collection of data. Laboratory and field tests were carried out to observe the performance of the mobile data logger system. The results showed that the performance of this system was acceptable.